Does time pressure impair performance? An experiment on queueing behavior - Anna Conte; Marco Scarsini; Oktay Sürücü (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
We experimentally explore the effects of time pressure on decision making. Under different time allowance conditions, subjects are presented with a queueing situation and asked to join one of two queues that differ in length, server speed, and entry fee. The results can be grouped under two main categories. The first one concerns the factors driving customers' decisions in a queueing system. Only a proportion of subjects behave rationally and use the relevant information effciently. The rest of the subjects seem to adopt a rule of thumb that ignores the information on server speed and follows the shorter queue. The second category is related to the effects of time pressure on decision performance. A significant proportion of the population is not affected by time limitations and shows a consistent behavior throughout the treatments. On the other hand, the majority of subjects' performance is impaired by time limitations. More importantly, this impairment is not due to the stringency of the limitation but mainly due to the fact that being exposed to a time limitation, even to a loose one, brings along stress and panic, and causes subjects to use time inefficiently.
urn:nbn:de:0070-pub-27244237
Keywords: C91; L00; C33; C35; 330; time pressure; queues with entry fee; join the shortest queue; experimentation; decision times